Respostas
respondido por:
48
y -8 +5y = -3 +2y +7
y +5y -2y = -3 +7 +8
6y - 2y = -3 + 15
4y = 12
y = 12/4
y = 3
y +5y -2y = -3 +7 +8
6y - 2y = -3 + 15
4y = 12
y = 12/4
y = 3
respondido por:
17
y-8+5y=-3+2y+7
-8+3-7=2y-y-5y
-12= - 4y
-4y=-12 multiplica tudo por.(-1)
4y=12
y= 12 =3 3 é a resposta exata por favor avalie. grato
4
-8+3-7=2y-y-5y
-12= - 4y
-4y=-12 multiplica tudo por.(-1)
4y=12
y= 12 =3 3 é a resposta exata por favor avalie. grato
4
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás